Peningkatan Kapasitas Masyarakat melalui Pelatihan Literasi Keuangan Keluarga di Desa Pondoknongko - Farida, Wiwik Mukholafatul; Iqbal, Achmad; Wulandari, Retno (Universitas Indraprasta PGRI, 2025)
Financial literacy is a crucial skill for individuals to effectively manage their financial resources and make sound financial decisions. However, the level of financial literacy in Indonesia remains low, which can negatively impact family financial well-being and overall economic stability. This community service activity aims to increase the capacity of the community, particularly housewives, in managing family finances through financial literacy training. The training was conducted online via the Google Meet platform on Wednesday, October 2, 2024, with 20 housewives from Pondoknongko Village, Kabat District, Banyuwangi Regency participating. The training methods included material presentation, discussion, and hands-on practice, covering topics such as financial health evaluation, household budgeting, saving, and avoiding excessive debt. Evaluation results showed that 90% of participants were satisfied with the delivered material and found the training beneficial for improving their financial literacy. The implications of this activity include improved family financial well-being, resilience in facing economic shocks, contribution to broader economic stability, and promotion of financial inclusion. Similar activities need to be continued and developed to provide a wider positive impact on society and the Indonesian economy.